Concinnity of dynamic inequalities designed on calculus of time scales - Sahir, Muhammad Jibril Shahab; Chaudhry, Faryal (Eurasian Mathematical Journal, 2024)
We present some reverse dynamic inequalities of Radon’s and Bergstr¨om’s type on time scales in general form. The extension of Clarkson’s dynamic inequality on time scales is also given. Our further investigations explore some dynamic inequalities by using Kantorovich’s and Specht’s ratios. The calculus of time scales unifies and extends continuous results and their corresponding discrete and quantum analogues.